The Correlation between FSTL1 Expression and Airway Remodeling in Asthmatics - Yahui Liu; Tian Liu; Jinxiang Wu; Tao Li; Xingai Jiao; Haiqing Zhang; Jiping Zhao; Junfei Wang; Lin Liu; Liuzhao Cao; Shuo Li; Jiawei Xu; et al. (Mediators of Inflammation)
Background. Asthma is characterized by airway remodeling. Follistatin-like protein 1 (FSTL1) is an extracellular glycoprotein. Recent studies suggest that FSTL1 may participate in the pathogenesis of asthma. Objectives. To analyze the association between FSTL1 and some parameters and inspect the role of FSTL1 in asthma. Methods. We examined FSTL1 levels in 32 asthmatics and 25 controls. All subjects enrolled had routine blood tests, spirometry, and impulse oscillometry performed. Additionally, 15 of the 32 asthmatics underwent fibre optic bronchoscopy. Spearman rank analysis was performed to detect the correlation between FSTL1 and other parameters. Results. Plasma FSTL1 levels were higher in asthmatics (130.762 ± 46.029 ng/mL) than in controls (95.408 ± 33.938 ng/mL) (p=0.009). Plasma FSTL1 levels were associated with fibrosis levels around the airways (rs=0.529, p=0.043) and α-smooth muscle actin (α-SMA) (rs=0.554, p=0.032). FSTL1 levels in bronchoalveolar lavage fluid were associated with collagen I (rs=0.536, p=0.040), α-SMA (rs=0.561, p=0.029), fibrosis levels (rs=0.779, p=0.001), and the thickness of the airway reticular basement membrane (RBM) (rs=0.660, p=0.007). Conclusions. FSTL1 levels in asthmatics were linked with increased smooth muscle mass and thickened RBM. FSTL1 may contribute to airway remodeling in asthmatics.